ANALISIS PARAMETER CURAH HUJAN DAN SUHU UDARA DI KOTA MAKASSAR TERKAIT FENOMENA PERUBAHAN IKLIM - Malino, Chaterina Restu; Arsyad, Muhammad; Palloan, Pariabti (Universitas Negeri Makassar, 2021)
Climate change is a global phenomenon that can be felt locally. The potential impact of climate change is a change in rainfall patterns and an increase in air temperature. One area that is vulnerable to climate change is urban areas, people and development are the driving factors for increasing greenhouse gas emissions. For climate change conditions in Makassar City, it is necessary to analyze the parameters of rainfall and air temperature. The data used are daily rainfall data and air temperature from 1991 - 2020 obtained from UPT BMKG Kelas I Maros. Data analysis was carried out by calculating the trend of rainfall and maximum air temperature, as well as calculating the frequency of rainfall with very heavy intensity (rainfall > 100 mm/day). The results of the analysis show an increase in the value for the rainfall parameter of 8.2 mm/year and the maximum air temperature of 0.0317 Â°C/year, but there is a decrease in heavy rainfall. Annual rainfall is increasing but the frequency of heavy rains is increasing from the occurrence of rain in Makassar City but will occur more often only with high intensity. Maximum air temperature can cause increased drought in the dry season, and increased rainfall can cause flooding in the rainy season.Keywords: rainfall, air temperature, trend